Enzymatic Synthesis of Oleyl Oleate, a Liquid Wax Ester, in a Stirred Tank Reactor - Mat Radzi, Salina (2006)
High performance enzymatic synthesis of oleyl oleate, a liquid wax ester was successfully synthesized via enzymatic esterification reaction of oleic acid and oley alcohol. Immobilised Candida antartica lipase B (Novozym 435) was used as biocatalyst. The study was divided into four parts which are the optimisation of reaction synthesis at different scales, the reactor study in term of mixing efficiency, the stability of immobilised enzyme and the analysis and characterization of the product of the reaction. Preliminary synthesis of oleyl oleate was carried out in a small scale reaction with a total volume of 3.5 mL using screw-capped vials. Optimisation reaction study via conventional method of varying one parameter at-a-time approach was carried out. A high percentage conversion yield of >90% was achieved at optimum reaction time of 5 min, reaction temperature of 40-6O0C1 molar ratio of substrates (oleyl alcoholloleic acid) of 2:1, amount of enzyme of 0.4 g and organic solvents of Log P23.5 at fixed agitation speed of 150 rpm. Investigation in larger scale production of oleyl oleate was performed using 2 L stirred tank reactor (STR). The reaction was scaled-up to 300X with a total volume of 1.05 L. A high percentage conversion of oleyl oleate was achieved of >95% by conventional experiment method at reaction time of 30 min, agitation speed of 400 rpm, reaction temperature of 45-50°C, molar ratio of substrate (oleyl alcoholloleic acid) of 2:l and amount of enzyme of 90 g. The reaction synthesis was further optimised by response surface method (RSM) based on five-level, three-variable central composite rotatable design (CCRD) to evaluate the interactive effects of important parameters in larger scale processing. Generally, simultaneously increasing amount of enzyme, agitation speed and reaction temperature would improved the yields. A high percentage conversion of 97.4% was achieved under the optimum condition, which compared well with the maximum predicted value of 97.7%. In order to improve the production and productivity of oleyl oleate to the highest amount that can be produced in a 2 L STR, the reaction was synthesized in a solvent-free system. Maximum scaling-up of substrate concentration that can be achieved in the reactor vessel was 900X as compared to 300X previously. The production and productivity of oleyl oleate were successfully improved from 295.39 g/L/h to 705.76 g1Uh and 31 0.16 glh to 952.78 glh, respectively. Reactor study on the performance of 2 L STR as a mixing device was evaluated to improve the mixing efficiency. The rheological property of the reaction mixture exhibited Newtonian behaviour. Rushton turbine impeller showed better performance in degree of mixing, as compared to AL Hydrofoil impeller whereby a high Reynolds number of >lo4 was achieved at 400 rpm, which exhibit a turbulent flow pattern. There was significant effect to the mixing improvement on the enzyme particles distribution by using a 2 impellers system with spacing of 30 mm. The enzyme showed high stability against heat as shown by the high percentage conversion of wax ester. Novozym 435 retained its synthetic activity up to 9 uses and 4 uses in screw-capped vials and STR, respectively. The effect of shear forces due to the mechanical agitation speed on the enzyme morphology was determined by scanning electron microscope (SEM). Although small rupture on the surface of enzyme was observed when increasing the agitation speed, the enzyme activity was very high even at high agitation speed.Analysis of product was evaluated by spectroscopy method of Fourier transform-infrared spectroscopy (FT-IR) and gas chromatography-mass spectroscopy (GC-MS) to identify the product obtained. Characteristics of oleyl oleate were also examined, which include iodine value, saponification value, acid value and ester value. Solubility of oleyl oleate in methanol and ethanol was comparatively lower as compared to the solubility at higher chain length of alcohols. This compound seems compatible in most of oils and stable even after heating up to 90°C and overnight storage at room temperature.